UMPSA hosts Malaysia Techlympics 2024 East Coast Zone Level - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 8 August 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is hosting the Malaysia Techlympics 2024 East Coast Zone Level, organized by the Ministry of Science, Technology, and Innovation (MOSTI).